Serious “human papillomavirus vaccine” game for Malaysian adolescents: development and preliminary study - Nur Hazreen Mohd Hasni; Akmal Asyraf Mior Azalian; Tuty Asmawaty Abdul Kadir; Mohd Azrul Hisham Mohd Adib (Intelektual Pustaka Media Utama, 2023)
In Malaysia, cervical cancer is the top three most common cancer among women. Vaccination and screening are mandatory for the prevention of the disease. Therefore, we aimed to develop a serious game for Malaysian adolescents, the